PEDAGOGICAL PSYCHOLOGICAL CAPABILITIES OF EXTRACURRICULAR ACTIVITIES IN THE DEVELOPMENT OF SOCIAL SOCIABILITY IN CHILDREN - Nigora Latipova Isakovna (American Journals, 2023)
In this article the pedagogical psychological capabilities of extracurricular activities in the development of social sociability in children are indicated.
Keywords: Extracurricular activities, social, psychological opportunity, activities.